Stall-regulated variable-speed wind turbine simulink model - Rosmin, N. (2013)
In this paper, a modular SIMULINK implementation of a stall-regulated variable-speed wind turbine (SRVSWT) model is described in a step-by-step approach. SIMULINK is chosen as the numerical environment in this work because it is a powerful modern software package that provides a convenient tool for simulation work instead of compilation of several program codes. With the modular system, each block solves one of the model equations. The preliminary results of the model characteristics for each block are presented. The authenticity of the developed sub-model is verified for each model before the combination of the full model is constructed. Methods for gathering the unavailable modelling data parameters are also discussed. Finally, the use of the model as a stall-regulated variable-speed wind turbine is demonstrated.